2019
DOI: 10.1016/j.jenvman.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the capability of magnetically separable Fe3O4/mordenite zeolite for refinery oily wastewater purification

Abstract: This is a repository copy of An investigation on the capability of magnetically separable Fe O /mordenite zeolite for refinery oily wastewater purification ₃ ₄ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…The broad peak of approximately 3400 cm −1 is related to the stretching vibration of H-O-H of the cinder/zeolite structure [35]. The peak at 1641 cm −1 is attributed to the H-O-H symmetric vibration of lattice water in the cinder/zeolite [36]. The peak intensity of 1641 cm −1 in synthetic zeolite and ZHLA is evidently enhanced because the pores and specific surface area are significantly higher than those in the cinder, which is capable of adsorbing more water.…”
Section: Zhla Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad peak of approximately 3400 cm −1 is related to the stretching vibration of H-O-H of the cinder/zeolite structure [35]. The peak at 1641 cm −1 is attributed to the H-O-H symmetric vibration of lattice water in the cinder/zeolite [36]. The peak intensity of 1641 cm −1 in synthetic zeolite and ZHLA is evidently enhanced because the pores and specific surface area are significantly higher than those in the cinder, which is capable of adsorbing more water.…”
Section: Zhla Characterizationmentioning
confidence: 99%
“…The peak intensity of 1641 cm −1 in synthetic zeolite and ZHLA is evidently enhanced because the pores and specific surface area are significantly higher than those in the cinder, which is capable of adsorbing more water. The peaks at 988 and 742 cm −1 are ascribed to the asymmetric stretching vibration of internal tetrahedral models of O-T-O bonds in TO 4 (where T denotes Si, Al, or Fe) and an external symmetrical stretching vibration of O-T-O bonds, respectively [33,36]. Phenolic hydroxyl groups and carboxylic acid groups are the two primary function groups in terms of the chelating chemistry of HA.…”
Section: Zhla Characterizationmentioning
confidence: 99%
“…The application of different physical and chemical treatments at the purification of waste materials is described in [24][25][26]. Now, let us pay attention to the properties of potential materials usable for microwave heating.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Moreover, response surface methodology was applied to optimize the removal condition and mechanism of Cr(Ⅵ) by Na2SO3/CaO (Zhao et al 2017). Besides, it has been shown that the response surface method is used to examine the potential of Fe3O4/mordenite zeolite for the purification of oily wastewater and observed that pH is the most important factor influencing Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) removal (Hesas et al 2019).…”
Section: Introductionmentioning
confidence: 99%